Detection and quantitation of lactoferrin in bovine whey samples by reversed-phase high-performance liquid chromatography on polystyrene–divinylbenzene - Palmano, Kate P; Elgar, David F (Journal of Chromatography A, 2002)
An existing RP-HPLC method for the measurement of the major bovine whey proteins in bovine whey samples and powders has been extended to include the analysis of the minor bovine whey protein lactoferrin. Lactoferrin could be detected and quantitated at levels down to 0.2 μg and linear calibration was observed between 0.2 and 30 μg. Reliable quantitation of lactoferrin in whey samples could be achieved provided the bovine serum albumin to lactoferrin ratio did not exceed 10:1. Quantitative data obtained by the RP-HPLC method compared favourably with data obtained by Mono S analytical chromatography.